Comparison of quality of life perception between migraineurs, diabetics and healthy volunteers through Brazilian SF-36 - Peixoto, Regina Mendonça; Rodrigues, Paula Roman; Chevtchouk, Liliana; Resende, Dilermando Fazito de; Jurno, Mauro Eduardo (Headache Medicine, 2012)
This study aimed to compare quality of life (QoL) among three groups of forty people each, consisting in a group of migraineurs, a group of diabetics and a group of healthy subjects. The three groups were submitted to the Brazilian version of SF-36, a questionnaire that includes eight domains: physical functioning, limitations due to physical aspects, pain, general health, vitality, social aspects, emotional aspects and mental health. Each item receives a score of 0-100, and patients were grouped into two groups: low QoL (0-60) a good QoL (61-100) points. The presence migraine or diabetes mellitus lead to a decrease in patients QoL that was greater in the migraineurs. The domains that appear to be most affected were physical functioning, limitations due to physical pain and mental health.